A Counter-Extrapolation Approach for the Boundary Velocity Calculation in Immersed Boundary Simulations. Issue 4 (21st April 2021) - Rezghi, Ali; Zhang, Junfeng
Abstract : The immersed boundary method (IBM) is often adopted to simulate various flow systems. The two key steps in IBM, namely the force distribution and velocity interpolation steps, are both performed in the immersed boundary layer region. As a result, the flow velocity in this area becomes less reliable, and the boundary velocity calculated from the local flow is less accurate. To enhance the boundary velocity accuracy, here we propose the counter-extrapolation method (CEM), which estimates the boundary velocity using the flow velocity outside of the immersed boundary layer, and thus effectively improved the accuracy in the calculated velocity. Several benchmark tests, which involve flat and curved boundaries and steady and unsteady flows, are conducted; and CEM is compared to other IBM variants recently proposed in the literature. Our results show remarkable accuracy improvements in flow velocity and flow-structure interaction from CEM compared to other methods.